1979
DOI: 10.3758/bf03197541
|View full text |Cite
|
Sign up to set email alerts
|

Age-of-acquisition effects in lexical and episodic memory tasks

Abstract: This paper reports four experiments on the effects of word age of acquisition in verbal tasks. In all cases, multiple-regression analysis was used to assess the relative effects of age as opposed to other potentially relevant word attributes. Experiments 1 and 2 concemed lexical memory tasks. In Experiment 1, picture naming speeds were found to be mainly determined by picture codability and name age of acquisition. In Experiment 2, it was found that when subjects produced words in response to bigram cues, earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
154
4

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(171 citation statements)
references
References 21 publications
13
154
4
Order By: Relevance
“…This is an estimate of the age at which the name of an object is learned, measured with subjective or objective values. Many studies report effects of subjective AoA on picture naming using retrospective adult rated estimates (Carroll & White, 1973;Gilhooly & Gilhooly, 1979;Morrison, Ellis, & Quinlan, 1992) and some studies also report effects of objective AoA-based on children's naming performance-on picture naming (Pind & Tryggvadottir, 2002). Morrison, Chappell, and Ellis (1997) observed a high correlation between rated and objective measures of AoA, and Ellis and Morrison (1998) found that both measures predict adult naming in their own study and in data published by Barry et al (1997) and Snodgrass and Yuditsky (1996).…”
mentioning
confidence: 84%
“…This is an estimate of the age at which the name of an object is learned, measured with subjective or objective values. Many studies report effects of subjective AoA on picture naming using retrospective adult rated estimates (Carroll & White, 1973;Gilhooly & Gilhooly, 1979;Morrison, Ellis, & Quinlan, 1992) and some studies also report effects of objective AoA-based on children's naming performance-on picture naming (Pind & Tryggvadottir, 2002). Morrison, Chappell, and Ellis (1997) observed a high correlation between rated and objective measures of AoA, and Ellis and Morrison (1998) found that both measures predict adult naming in their own study and in data published by Barry et al (1997) and Snodgrass and Yuditsky (1996).…”
mentioning
confidence: 84%
“…Using a number of experimental paradigms, researchers have shown that the age of word acquisition significantly affects the speed and accuracy with which a word is accessed and processed (Barry, Morrison, & Ellis, 1997;Cuetos, Ellis, & Alvarez, 1999;Ellis & Morrison, 1998;Gerhand & Barry, 1998Gilhooly & Gilhooly, 1979;Lewis, 1999;Meschyan & Hernandez, 2002;Morrison, Chappell, & Ellis, 1997;Morrison & Ellis, 1995. Early learned words typically elicit faster response times than late learned words in word reading, auditory and visual lexical decision, picture naming, and face recognition.…”
Section: Age Of Acquisition In Monolingual Individualsmentioning
confidence: 99%
“…ever, WF and AoA are naturally confounded, with earlyacquired words tending to be higher in frequency than lateacquired words (Carroll & White, 1973;Gilhooly & Gilhooly, 1979;Morrison et al, 1992). Furthermore, initial investigations of the simultaneous effects of WF and AoA found an effect of AoA, but no effect of WF on objectnaming speed was found after accounting for effects of AoA (Carroll & White, 1973;Gilhooly & Gilhooly, 1979;Morrison et al, 1992).…”
mentioning
confidence: 99%
“…Furthermore, initial investigations of the simultaneous effects of WF and AoA found an effect of AoA, but no effect of WF on objectnaming speed was found after accounting for effects of AoA (Carroll & White, 1973;Gilhooly & Gilhooly, 1979;Morrison et al, 1992). However, subsequent studies have established distinguishable effects of WF and AoA (e.g., Barry et al, 1997;Ellis & Morrison, 1998, Experiment 1;Lachman, 1973;Lachman, Shaffer, & Hennrikus, 1974).…”
mentioning
confidence: 99%